Virtual Reality of Animated Lung with Internal Structures. Issue 1 (July 2017) - Nakagawa, Bruno T.; Penteado, Rafael V.S.; Tsuzuki, Marcos S.G.; Tori, Romero; Takimoto, Rogério Y.; Martins, Thiago C.; Abe, Leonardo I.; Rosso, Roberto S.U.; Gotoh, Toshiyuki; Iwasawa, Tae
Abstract: Virtual bronchoscopy is a promising method for diagnosing pulmonary disorders. It is an alternative diagnostic modality when flexible bronchoscopy is not available. The visualization of the lung movement, particularly the airways respiratory movement is a very active research topic. This work combines both areas, creating the possibility of an animated virtual bronchoscopy. The virtual bronchoscopy is happening while the breathing of the patient is simulated happening. The respiratory movement is extracted from a sequence of low resolution CT images and registered to a CT image with high resolution. The animated model is visualized in a immersing environment where the movements are controlled by the Oculus Rift and the Leap Motion.